Unsuccessful Attempt at Reversing Intractable Ventricular Arrhythmia in a Post CABG Patient - Siraj, Masoom; Rahman, Md Hamidur; Yasmin, Farzana (Ibrahim Cardiac Medical Journal, 2011)
The case of a 58 years old, gentleman is described here who underwent an emergency Coronary Artery Bypass Grafting (CABG) at Ibrahim Cardiac Hospital & Research Institute. Right after the procedure he started developing ventricular arrhythmias. We present here the various challenges that we had to face and the options available to us in the setting of a third world hospital to manage a case of intractable ventricular arrhythmia. The patient underwent revascularization, intra-aortic balloon pump support, pharmacological manipulation, burst pacing with over drive suppression and cardio-version. Yet we were unable to control the fatal ventricular arrhythmia with an unfavorable outcome. Our case stands out from the rest as arrhythmia started after revascularization as opposed to many a case that is treated by revascularization. Ibrahim Card Med J 2011; 1(1):56-58